1985
DOI: 10.1126/science.2988128
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Modeling of an Autonomously Oscillatory Circadian Clock in Euglena

Abstract: Eukaryotic microorganisms, as well as higher animals and plants, display many autonomous physiological and biochemical rhythmicities having periods approximating 24 hours. In an attempt to determine the nature of the timing mechanisms that are responsible for these circadian periodicities, two primary operational assumptions were postulated. Both the perturbation of a putative element of a circadian clock within its normal oscillatory range and the direct activation as well as the inhibition of such an element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
3

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(45 citation statements)
references
References 35 publications
0
42
0
3
Order By: Relevance
“…The ability of calmodulin antagonists to alter the phase of the photosynthesis rhythm was examined by exposing cells to 2 h pulses ofa particular antagonist. At the beginning of the transition from dark to light, when the culture was at a density of 8 x 104 cells ml1', the light intensity was adjusted to 3.5 1uE m-2 s-' for the following 4 (7). To ensure that a potential phase shift would be observed, each of the three antagonists were pulsed at six separate times during the h 7 to 26 of constant light conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of calmodulin antagonists to alter the phase of the photosynthesis rhythm was examined by exposing cells to 2 h pulses ofa particular antagonist. At the beginning of the transition from dark to light, when the culture was at a density of 8 x 104 cells ml1', the light intensity was adjusted to 3.5 1uE m-2 s-' for the following 4 (7). To ensure that a potential phase shift would be observed, each of the three antagonists were pulsed at six separate times during the h 7 to 26 of constant light conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The biochemical basis for the biological clock is unknown and it is not certain whether cells have one master clock controlling all circadian rhythms, or whether multiple clocks control specific subsets ofrhythmic processes. The circadian rhythms ofEuglena have been extensively studied (3) and recently a feedback loop involving Ca2" and calmodulin was proposed in an attempt to define biochemically components of the clock controlling the Euglena cell division rhythm (7). The rationale for proposing calmodulin involvement was based on the observation that exposure to a calmodulin antagonist results in phase shifting (timing advances or delays) of the monitored cell division rhythm (7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We concluded that the metabolism of calcium is important for clock functions from the late subjective day phase to the early subjective night phase (Nakashima, 1984(Nakashima, , 1986. Important roles for calcium in clock functions have also been indicated in other organisms, such as Aplysia (Eskin & Corrent, 1977) and Euglena (Goto et al, 1985;Tamponnet & Edmunds, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Gonyaulax (hoje Linguludinium), Euglena, Chlamydomonas e Acetabularia (DRIESSCHE; BONOTTO, 1969;GOTO et al, 1985;LOPES et al, 2002;MORSE et al, 1989). Desses estudos foi concluído que osciladores pós-traducionais também existem em eucariotos.…”
Section: Resultados Importantes Foram Obtidos Em Eucariotos Fotossintunclassified